Towards new cholera prophylactics and treatment: Crystal structures of bacterial enterotoxins in complex with GM1 mimics - Julie Elisabeth Heggelund; Alasdair Mackenzie; Tobias Martinsen; Joel Benjamin Heim; Pavel Cheshev; Anna Bernardi; Ute Krengel (Scientific Reports, 2017)
Abstract Cholera is a life-threatening disease in many countries, and new drugs are clearly needed. C-glycosidic antagonists may serve such a purpose. Here we report atomic-resolution crystal structures of three such compounds in complexes with the cholera toxin. The structures give unprecedented atomic details of the molecular interactions and show how the inhibitors efficiently block the GM1 binding site. These molecules are well suited for development into low-cost prophylactic drugs, due to their relatively easy synthesis and their resistance to glycolytic enzymes. One of the compounds links two toxin B-pentamers in the crystal structure, which may yield improved inhibition through the formation of toxin aggregates. These structures can spark the improved design of GM1 mimics, either alone or as multivalent inhibitors connecting multiple GM1-binding sites. Future developments may further include compounds that link the primary and secondary binding sites. Serving as decoys, receptor mimics may lessen symptoms while avoiding the use of antibiotics.